1939
DOI: 10.1021/j150394a010
|View full text |Cite
|
Sign up to set email alerts
|

Sol and Gel in Hevea Latex and Crude Rubber. Influence of Oxidation on Gel–Sol Transformation.

Abstract: From the work of Caspar! (1), Feuchter (2), and others it is now well known that a large proportion of the hydrocarbon in unmasticated crude Hevea rubber diffuses into and is therefore soluble in petroleum ether or ethyl ether when the rubber is covered with these solvents and allowed to stand at room temperature. This soluble form of rubber has been termed "sol," and the residue from a prolonged and repeated solvent extraction is known as the gel skeleton, which contains practically all of the protein and ash… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1939
1939
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…In this case it is shown that gel can be fractionated in hexane which contains 10 per cent of absolute alcohol and that the solubility diminishes as extraction proceeds. This evidence, together with that recently obtained (1) showing the high resistance of a portion of latex gel to oxidation, leads to the conclusion that the rubber gel in latex is present in variable molecular sizes.…”
Section: Stability Of Rubber In Hexane and Tetralinsupporting
confidence: 67%
See 1 more Smart Citation
“…In this case it is shown that gel can be fractionated in hexane which contains 10 per cent of absolute alcohol and that the solubility diminishes as extraction proceeds. This evidence, together with that recently obtained (1) showing the high resistance of a portion of latex gel to oxidation, leads to the conclusion that the rubber gel in latex is present in variable molecular sizes.…”
Section: Stability Of Rubber In Hexane and Tetralinsupporting
confidence: 67%
“…MOLECULAR WEIGHT OF MILLED CREPE FRACTIONS Fractionation of milled crepe was carried out by the procedure already referred to (1). The molecular weight data on these fractions are given in table 5.…”
Section: Molecular Weight Range Of Sol In Crepementioning
confidence: 99%
“…Since these authors did not determine the molecular weight of the different fractions, an attempt was made to repeat this work on the R. C. . A. crepe employed in this and previous studies (5,6). It was found that this crepe did not dissolve completely in the mixed solvent at 50°C ., and when cooled to 42°the viscosity was so high that the gel could not be readily separated from the solution.…”
Section: Fractionation Of Rubbermentioning
confidence: 74%
“…A. (Rubber Culture Maatschappij Amsterdam) crepe previously studied (5,6) or smoked sheet to avoid differences due to sample variations. The amount of rubber in solution was determined by drying 25 cc.…”
Section: Solubility and Molecular Weight Of Crude Rubbermentioning
confidence: 99%
“…Pummerer (17,18) termed the ether-soluble part the "sol" fraction and the ether-insoluble part, the "gel" fraction. More recently Kemp and Peters (9,10,11) and Bloomfield and portions depends on the type of solvent used and other conditions of extraction. Although the method of Pummerer produces only a rough separation, it was chosen as a convenient starting point for the electron microscope examination of rubber fractions, and the terms "sol" and "gel" will refer here to fractions obtained by this method.…”
Section: Unvulcanized Rubbermentioning
confidence: 99%